Coronary Artery Spasm- An Uncommon Condition after CABG (Global Journal of Medical Research, 2020)
Aim: Coronary artery bypass grafting (CABG) is one of the most common cardiac surgery done in Hong Kong for ischemic heart diseases. We report a case of a 55-year-old man who demonstrated native coronary artery spasm following on-pump CABG which was managed by intra-aortic balloon pump (IABP) insertion and vasodilators. Method: A 55-year-old man, ex-smoker, with history of PVD, presented with unstable angina. CABG was performed and the procedure was unremarkable. 2 hours after operation, patient developed sudden cardiac arrest. Bedside sternotomy was performed, findings was unremarkable. IABP was inserted and later further supported by VA ECMO. Coronary angiogram showed diffuse spasm all three native major coronary arteries, demonstrating competitive flow. All three native coronary arteries responded to Glyceryl trinitrate (GTN) infusion. Two bypass graft (LSV and LIMA) was patent. The coronary artery spasm improved with continuous GTN infusion.
Keywords: CABG; coronary artery spasm